(untitled) (Journal of the College of Basic Education, 2024)
The problem of the research is that there is a decline in the level of culture and nutritional awareness of first-year female students in the kindergarten department. Therefore, the researcher decided to find the relationship between nutritional awareness and happiness for female students in order to give them some concepts of nutritional and health culture and awareness of them. The aim of the research was to find out the relationship between nutritional awareness and the level of happiness among female students in the kindergarten department. To achieve this, the research was conducted on a sample of (120) female students from the kindergarten department. Kindergarten / College of Basic Education / Al-Mustansiriya University, a questionnaire measuring nutritional awareness was applied to them, which consisted of (28) items, and a questionnaire measuring happiness, which consisted of (27) items. The researcher used SPSS to process the statistical data. The results of the research showed that the degree of general nutritional awareness Among female students in the first stage, it was acceptable, and the results indicated that there were statistically significant differences in the degree of nutritional awareness and happiness. The researcher recommended several recommendations, the most important of which is the need to pay attention to nutritional and health education methods, such as lectures, seminars, and media outlets, to spread food culture and health awareness, especially for students, and to provide them with the foundations of correct nutrition and knowledge of the importance of different nutritional elements to prevent malnutrition and various diseases. The necessity of gradualness and continuity in nutritional curricula and enriching the curriculum with information, theoretical nutritional concepts, and practical skills in a way that leads to interconnection between theory and practice.